ISIS, GENOCIDE AND A â€œTHICK DESCRIPTIONâ€ OF POWER - Nazala, Rochdi Mohan (Jurnal Transformasi Global, 2019)
IntroductionOn August 3, 2015, Islamic State in Iraq and Syria (ISIS) fighters were marching with full military equipment to Kocho, a village that belongs to Yazidi, one of the minorities in Iraq, near Mount Sinjar (Kikoler, 2015). They captured 1200 men, women and children whom in the next two days ISIS told to leave their religious practice, which is a combination of elements of Zoroastrianism, Judaism, Christianity, and Islam and to convert to Islam. When the majority of Yazidi's men refused the demand, all of them were taken with their eyes blindfolded around 500 meters outside the village, and upon arriving at the destination, they were lined up, videotaped and shot (Amnesty International Canada, August 18, 2014). The women became sex slaves (Smith, 2014) and the children were transferred to ISISâ€™s camp to train as soldiers (McLaughlin, 2016).The story above from Kocho is a one of frames that is used repeatedly to justify the allegation of ISIS conducting genocide toward Yazidi as well as other minorities in Iraq and Syria. The European Union, for instance, announced in the beginning of 2016 that ISIS was "committing genocide against Christians and Yazidis, and other religious and ethnic minorities (Brown, 2016). Later, this statement was followed by the announcement of the US government in March 2016 that stated ISIS â€œis responsible for genocide against groups in areas under its control, including Yazidis, Christian and Shiite Muslimsâ€ (Labott & Kopan, 2016).Â HuyÂ  (2010) in his comment on the book of one Khmer Rougeâ€™s survivor, Bou Meng, says genocide â€œhas always been a political act, and always will be.â€ Politics, according to Morgenthou (1985), is about interest defining in terms of power. Indeed, as one of the ISIS's fighters says above, by joining ISIS and subsequently becoming involved in genocidal acts, it brings them the feeling of being free. According to the Oxford English Dictionary (OED), to be free means to be â€œable to act as one wishes, determining oneâ€™s own action or choice; done or made without compulsion or constraintâ€ (Oxford English Dictionary online, 2016). In other words, the perpetrators acknowledge that their ruthless behaviors are the sign of power because, as it is written in the OED, power creates a sense of theÂ  â€œability to act or affect something strongly; [exhibiting] physical or mental strengthâ€ (Oxford English Dictionary online, 2016).Â How can genocidal acts be political while also creating a sense of power within the perpetrators?Â  To what extent do the atrocious acts of mass killings, sex slavery as well as human trafficking involving children create a sense of power to ISISâ€™s fighters? This essay aims to construct a "thick description" of power within ISISâ€™s genocidal acts. The ideas brought forth is that genocide as it was against Yazidi reflects the meaning ISISâ€™s members give to power and how it operates in social life.Â